Effect of Pectin on the Characteristics of Edible Film from Skin Gelatin of Red Snapper (Lutjanus argentimaculatus) - Rahmi Nurdiani; Hefti Salis Yufidasari; Joys Sandralina Sherani (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
The aim of this research was to determine the effect of addition of pectin on characteristics of edible film from gelatin of red snapper (Lutjanus argentimacalatus) skin. Concentration of pectin used were 0%, 0.2%, 0.4%, 0.6%, 0.8% and 1%. Water content, thickness, tensile strength, elongation, and the transmition rate of the water vapor of edible film were analysed. Results from analysis of variance showed that different concentration of pectin significantly affected (P<0.05) on the water content, thickness, tensile strength, elongation, and transmition rate of water vapor of edible film. Therefore, it was suggested that addition of 0.6% of pectin showed a good quality of edible film and in accordance with the Japan International Standard (JIS).